Is liquid biopsy the future commutator of decision-making in liver transplantation for hepatocellular carcinoma? - Gonvers, Stéphanie; Tabrizian, Parissa; Melloul, Emmanuel; Dormond, Olivier; Schwartz, Myron; Demartines, Nicolas; Labgaa, Ismail (Frontiers in Oncology, 2022)
Liver transplant (LT) is the most favorable treatment option for patients with early stage hepatocellular carcinoma (HCC). Numerous attempts have been pursued to establish eligibility criteria and select HCC patients for LT, leading to various systems that essentially integrate clinico-morphological variables. Lacking of sufficient granularity to recapitulate the biological complexity of the disease, all these alternatives display substantial limitations and are thus undeniably imperfect. Liquid biopsy, defined as the molecular analysis of circulating analytes released by a cancer into the bloodstream, was revealed as an incomparable tool in the management of cancers, including HCC. It appears as an ideal candidate to refine selection criteria of LT in HCC. The present comprehensive review analyzed the available literature on this topic. Data in the field, however, remain scarce with only 17 studies. Although rare, these studies provided important and encouraging findings highlighting notable prognostic values and supporting the contribution of liquid biopsy in this specific clinical scenario. These results underpinned the critical and urgent need to intensify and accelerate research on liquid biopsy, in order to determine whether and how liquid biopsy may be integrated in the decision-making of LT in HCC.